Digital Transformation through e-Government in Indonesia's Governance and Its Impact on Reducing Corruption Levels - Adji Yuwana Pratama; Ridwan Ridwan; Mardy Serey (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
Digital development and globalization have encouraged many countries to implement e-Government in order to improve transparency, efficiency, and public participation in government. This study focuses on the implementation of e-Government in Indonesia, with the aim of measuring its impact in reducing corruption and identifying the challenges faced in the implementation process. In addition, this study also looks at the possibility of new forms of corruption arising as a result of digitalization, known as digital corruption. This study uses a descriptive qualitative approach by collecting secondary data from various relevant literature sources. The results show that although e-Government aims to reduce corruption, corruption rates in Indonesia have actually increased after the implementation of the Electronic-Based Government System (SPBE). The main challenges identified include a large digital divide, low digital literacy among officials and the public, and weak oversight of e-Government implementation. In addition, there is potential for digital corruption, such as data manipulation and system abuse, which could cause harm. This study provides an understanding of how e-Government in Indonesia has not yet been fully successful in reducing corruption rates. These findings also indicate the need for increased digital literacy and stricter supervision to prevent digital corruption.Perkembangan digital dan globalisasi mendorong banyak negara untuk menerapkan e-Government guna meningkatkan transparansi, efisiensi, dan partisipasi publik dalam pemerintahan. Penelitian ini fokus pada penerapan e-Government di Indonesia, dengan tujuan untuk mengukur dampaknya dalam mengurangi korupsi serta mengidentifikasi tantangan yang dihadapi dalam proses implementasinya. Selain itu, penelitian ini juga melihat kemungkinan munculnya bentuk korupsi baru akibat digitalisasi, yang dikenal dengan istilah digital corruption. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan mengumpulkan data sekunder dari berbagai sumber literatur yang relevan. Hasil penelitian menunjukkan bahwa meskipun e-Government bertujuan untuk mengurangi korupsi, angka korupsi di Indonesia justru meningkat setelah penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE). Tantangan utama yang ditemukan termasuk kesenjangan digital yang masih besar, rendahnya literasi digital di kalangan pejabat dan masyarakat, serta lemahnya pengawasan terhadap implementasi e-Government. Selain itu, ditemukan adanya potensi digital corruption, seperti manipulasi data dan penyalahgunaan sistem yang berpotensi merugikan. Penelitian ini memberikan pemahaman tentang bagaimana e-Government di Indonesia belum berhasil sepenuhnya menurunkan angka korupsi. Temuan ini juga menunjukkan perlunya peningkatan literasi digital dan pengawasan yang lebih ketat agar digital corruption dapat dihindari.